2008
DOI: 10.1007/s11010-008-9957-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of toll-like receptor 3, RIG-I and MDA5 in poly (I:C) RNA-induced mesothelial inflammation

Abstract: Viral inflammation and infection of mesothelial cells (MC) are a major problem in several organ systems including pleura, pericardium and peritoneum. Toll-like receptors (TLRs) are an essential part of the innate immune system for early recognition of pathogen-associated molecular patterns. TLRs recognise molecular patterns associated with microbial pathogens and induce an immune response. TLR3 recognises dsRNA of viral origin as exemplified by poly (I:C) RNA, a synthetic analogue of viral dsRNA. The helicases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Canonically, RIG-I is regarded as an intracellular RNA receptor because cytosolic expression has been reported for dendritic cells, monocytes, mesothelial cells, monocytes/PBMCs, and other cell types (1,9,18,22). In line with these previously reported cell types, we detected RIG-I protein expression in cytosolic neutrophil fractions at a similar molecular mass as in PBMCs, which are well known to express cytosolic RIG-I.…”
Section: Discussionsupporting
confidence: 85%
“…Canonically, RIG-I is regarded as an intracellular RNA receptor because cytosolic expression has been reported for dendritic cells, monocytes, mesothelial cells, monocytes/PBMCs, and other cell types (1,9,18,22). In line with these previously reported cell types, we detected RIG-I protein expression in cytosolic neutrophil fractions at a similar molecular mass as in PBMCs, which are well known to express cytosolic RIG-I.…”
Section: Discussionsupporting
confidence: 85%
“…TLRs recognize conserved pathogen-associated molecular patterns and are expressed not only on immune cells but also on a number of non-immune cells [25,26]. An expression of several TLRs on human MC was shown before [27]. TLRs recognize molecular patterns associated with microbial pathogens and induce an immune response [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown previously the efficiency of receptor knockdowns with these siRNAs, which result in a significant downregulation of the basal expression of TLR3 (86%), RIG-I (89%), and MDA5 (90%), whose TLR3 and RIG-I synthesis was confirmed at the protein level (26). In the actual experiments, transfection of cells with siRNA specific for TLR3 and RIG-I significantly blocked the poly(I:C) RNA-induced increase in IP-10 expression and synthesis ( Fig.…”
Section: Interferon-inducible Protein 10 (Ip-10) Is a Chemokine Playimentioning
confidence: 79%
“…The helicases retinoic acidinducible gene I (RIG-I) and melanoma differentiation-associated gene 5 (MDA5) may also act as sensors of viral infections through recognition of viral dsRNA (15,23,27). We have previously shown that human MC express TLR3, RIG-I, and MDA5 and that activation of these viral receptors upregulates several cytokines and chemokines (25,26).…”
Section: Interferon-inducible Protein 10 (Ip-10) Is a Chemokine Playimentioning
confidence: 99%